EU Cohesion Policy Implementation - Evaluation Challenges and Opportunities The 1st International Conference on Evaluating Challenges in the Implementation of EU Cohesion Policy (EvEUCoP 2022), Coimbra, 2022 - Henriques, Carla; Viseu, Clara (Springer Proceedings in Political Science and International Relations, 2023)
This open access book is the result of the 1st International Conference on Evaluating Challenges in the Implementation of EU Cohesion Policy (EvEUCoP 2022). It presents the recent findings, sparks discussion, and reveals new research paths addressing the use of novel methodologies and approaches to tackle the challenges and opportunities that are unveiled with the implementation of the EU cohesion policy. The authors cover a wide range of topics including the monitoring of data; the clearness of indicators in measuring the impact of interventions; novel evaluation methods, addressing the mid-term and terminal assessment; as well as case studies and applications on evaluations of the thematic objectives under the scrutiny of the cohesion policy, namely: • Research, technological development, and innovation; • Information and communication technologies; • Shift toward a low-carbon economy. During the 2014-2020 programmatic period, member states were required to undertake assessments to evaluate the efficacy, efficiency, and impact of each operational program. Such evaluations are generally concerned with the compliance of projects and activities with programmatic priorities, as well as with funds' absorption capacity and refer to ex-ante and ex-post assessments. Hence, this book proposes the use of novel methodologies addressing the mid-term and terminal assessments that enable performing the efficiency appraisal of the operational programs and that can support decision-makers in the selection of projects that should be awarded for funding.